Reflecting Contemporary Design Research - Engholm, Ida (FormAkademisk, 2017)
In recent years, design research has been the object of growing attention in universities and academies throughout the world. The present article addresses the heterogeneous character of design research and the current need for reflection on the various approaches and interests. For this purpose, the paper follows two steps. First, it proposes a categorization of the field in the form of a position model. The article's underlying assumption is that design research as a discipline exists in many different forms that cannot necessarily be brought together under one common academic research tradition; instead it is necessary to attempt to define the field in order to initiate discussions about what constitutes the various research bases for design. Second, the article discusses the implication for future design research when it is an interdisciplinary field that involves many disciplines, mindsets and methodological practices.